UPLB Museum of Natural History center for Philippine Biodiversity - Santos, Dannielle Edrienne D.; De Leon, Ruby Teresa M. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The Museum of Natural History was established in 1976 by the University of the Philippines to become the center of research, documentation, and repository of specimens for scientific reference, information and education on Philippine biodiversity and its conservation. It holds some of the largest collections of biological specimens in the Philippines, including mammals, plants, and the first microbial and algal culture collection to be registered with the World Federation of Culture Collections. Since 1993, the Museum's home is the old Makiling Residence hall at the Foothills of Mount Makiling. However, it is already old and structurally unsound for a museum that accommodates about 50,000 visitors per year. On top of that, there is a severe lack of space for other exhibits and built-in research facilities. The project is a redesign of the Museum of Natural History, which aims to provide a better home for the priceless collections of the university by creating larger exhibition spaces, as well as include in-house research facilities for researchers, staff, and students alike. The museum also aims to showcase these collections for educational purposes and to promote Philippine biodiversity. Outdoor activities are also included to provide a better museum experience and gain a broader audience.
Includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Museum of Natural History (Los Banos).; Museums